THE COUNTERPARTY’S SUPERIOR BARGAINING POSITION AS A FACTOR SHAPING THE EXPRESSION OF WILL. - Hovhannisyan, Arsen (State and Law, 2026)
This article explores the legal implications of a counterparty's superior bargaining position as a factor shaping the expression of will in civil transactions. Anchored in classical and modern civil law theory, the study examines how imbalances in negotiating power—rooted in economic dominance, infrastructure control, or market dependence—can distort the autonomy of will, raising questions about the validity of the resulting contracts. The Armenian legal framework, particularly the Civil Code and the Law on Protection of Economic Competition, is analyzed to demonstrate how abuse of superior bargaining position may constitute a defect of will and render a transaction disputable. Drawing on jurisprudence, legal doctrine, and regulatory practice, the article argues that such abuse, even in the absence of traditional vitiating factors like coercion or fraud, can undermine genuine consent. It concludes that transactions concluded under these conditions should be assessed through a hybrid lens of civil and competition law, particularly where an administrative act has confirmed the abuse.
Keywords: Superior Bargaining Position; Defect of Will; Contractual Autonomy; Abuse of Economic Power; Civil Transaction Validity